Faktor-faktor yang Berhubungan dengan Kepatuhan Minum Obat Pasien Skizofrenia di RSJ. PROF. DR. HB. SAANIN Padang: Factors Associated with Adherence to Taking Medication for Schizophrenia Patients at the RSJ. PROF. DR. HB. SAANIN Padang - Ira Erwina; Dewi Eka Putri; Bunga Permata Wenny (NERS Jurnal Keperawatan, 2015)
Schizophrenia is one of the mental disorders with the highest number when compared with other mental disorders. The problem faced today is the high rate of relapse in patients with schizophrenia. Some of the factors that affect treatment compliance is the effect of drugs taken, drug dosage, duration of treatment and the cost of treatment. The purpose of this study is to determine the factors associated with treatment compliance. The study was conducted in Prof.Dr.Hb.Saanin Mental Hospital Padang; the number of respondents as many as 75 people, cross-sectional design, the data collected using questionnaires. The results showed that there is a significant relationship (p <0.05) between the side effects of medication and dosage to the patient's adherence to treatment, and there was no significant relationship (p> 0.05) between duration of treatment and the cost of treatment with patient compliance with treatment. The most influential factor is the dose of the drug. It is recommended for nurses to constantly monitor the patient in taking medication and for patients to always communicate the perceived effects while taking the drug.